Historical Analysis of Tourism Policy and Planning in Malta - Mifsud, Maria (2006)
Tourism development is an activity that while bringing vast economic advantages, it canalso have negative social and environmental impacts. Hence, if tourism is not properlyplanned it can become a very unsustainable activity. The overwhelming message in many studies, papers and reports is that positive impacts can be maximized and negative ones minimized by means of intelligent policy frameworks [and] sound public and private sector forward planning(Jeffries, 2001:25). Literature has shown that the state plays an indispensable role in successful tourism development since the centralisation of policy-making powers in the hands of the state allows appropriate measures for the creation of a suitable framework for the promotion and development of tourism to be taken.